KONSTRUKSI GENDER PEREMPUAN KELAS MENENGAH DALAM PILIHAN PRODUK-PRODUK KESEHATAN DI PERUMAHAN LINGKAR PRATAMA KOTA MATARAM - Putri Anggun Nurrahmi Amalia; Saiful Hamdi; Taufiq Ramdani (Indonesian Journal of Social Sciences and Humanities, 2020)
This study aims to determine the effect of gender construction on the choice of health products, the impact of the choice of health products on changes in social status in society for middle-class women and the community's response to middle-class women who use health products in Lingkar Pratama Housing, Mataram City. The theory used as an analysis in this study is the theory of social construction proposed by Peter L. Berger and Luckmann. This study used a qualitative, research method with a phenomenological design. Based on the research results, the influence of gender construction among middle-class women living in Lingkar Pratama Housing is very strong, this is evidenced by the large number of middle-class women who own and use various kinds of health and beauty products in their homes. Then formed three dialectical moments, namely Objectivation (Cognitive), Internalization (Affective), and Externalization (Psychomotor). As for the impact felt by middle-class women after using health and beauty products, they experience increased self-confidence in socializing in their social environment, experiencing changes in appearance and changes in income that have increased. Then the community response is that they consider it reasonable and agree to see how the life and lifestyle of middle-class women who live in the Mataram City Primary Circle Housing.